(untitled) (Journal of the College of Basic Education, 2023)
Two organic inhibitors namely 2-amino[4-p-Bromophenyl]Thiazole (ABT) and 2-amino[4-p-Hydroxyphenyl]Thiazole (AHT) were synthesized. FTIR and NMR studies were done in order to confirm the composition of the synthesized inhibitors. These compounds were evaluated as inhibitors for Aluminum in (0.02M) NaOH solutions by weight loss and potentiodynamic polarization techniques. Different concentrations of inhibitors, temperatures, and immersion time have been tested. Values of inhibition efficiency obtained from the two methods are in good agreement and are dependent upon the concentration of inhibitor. The results observed have been discussed in the light of the molecular structures of the compounds and their adsorption on the surface of the corroding meta